Microbial diversity and functional genes of red vinasse acid based on metagenome analysis - Lv, Jianman; Ye, Yaolu; Zhong, Yuan; Liu, Wukang; Chen, Meilin; Guo, Ailing; Lv, Jun; Ma, Huawei (Frontiers in Microbiology, 2022)
Red vinasse acid has a distinct flavor and a vivid red color that are directly tied to the intricate metabolic activities of microorganisms that produce it. In this study, metagenomic technology was used to mine its functional genes and examine the microbial diversity of red vinasse acid. The findings revealed the identification of 2,609 species, 782 genera, and 63 phyla of microorganisms, and the dominant genus was Lactobacillus. Amino acid metabolism and carbohydrate metabolism were significant activities among the 16093 and 49652 genes that were annotated in the eggNOG and KEGG databases, respectively. In gluconeogenesis, red vinasse acid encodes 194 genes controlling the transporter protein systems of different sugars and has key enzyme genes that catalyze the conversion of intracellular sugars into glycolytic intermediates. In amino acid flavor formation, red vinasse acid contains 32 control genes for branched-chain aminotransferase (BcAT), 27 control genes for aromatic-amino-acid transaminase (ArAT), 60 control genes for keto acid invertase, 123 control genes for alcohol/aldehyde dehydrogenase, and 27 control genes for acetyl esterase, which have the basis for the formation of strong flavor substances from amino acids.